2017
DOI: 10.5530/ijopp.10.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Diabetes Related Knowledge, Attitude and Practice among Diabetics and Non-diabetics using Self Prepared Questionnaire for Awareness of Health Promotion

Abstract: Introduction: As diabetes mellitus is one of the most challenging public health problem in 21st century, it is important to know about the awareness level of a disease condition in a population, which plays a vital role in future development, early detection and prevention of disease. Objective: To assess the awareness and knowledge regarding diabetes mellitus among diabetic and non-diabetic subjects. Methods: A prospective and observational study was done in 100 diabetic and 50 non-diabetic subjects. All in-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 9 publications
2
14
1
Order By: Relevance
“…The majority of female respondent sexes were 74% as shown in Table 1. This condition was different from the research conducted by Konduru et al who stated that the majority of diabetic respondents in male Indian multispecialist hospitals were 64%; [11] besides, other studies have shown that male sufferers outnumber women. [12] The differences in these characteristics are likely to occur because respondents were taken from the puskesmas patients who were Prolanis participants, so the possibility of female sufferers being more orderly in control to the puskesmas and more interested in attending the counseling conducted by researchers.…”
Section: Resultscontrasting
confidence: 78%
“…The majority of female respondent sexes were 74% as shown in Table 1. This condition was different from the research conducted by Konduru et al who stated that the majority of diabetic respondents in male Indian multispecialist hospitals were 64%; [11] besides, other studies have shown that male sufferers outnumber women. [12] The differences in these characteristics are likely to occur because respondents were taken from the puskesmas patients who were Prolanis participants, so the possibility of female sufferers being more orderly in control to the puskesmas and more interested in attending the counseling conducted by researchers.…”
Section: Resultscontrasting
confidence: 78%
“…A previous study done in Ghana by Obirikorang et al [ 20 ] found out that, participants knew diabetic foot (51.5%), hypertension (35.4%), neuropathy (29.2%), hypoactive sexual arousal (25.4%), arousal disorder (21.5%), retinopathy (17.7%), heart disease (9.2%), and nephropathy (5.4%) as the most common DM complications. Another study by Konduru, Ranjan, Karthik and Shaik [ 38 ] revealed that eye complications (69%) was commonly known by diabetic patients followed by cardiac complications (51%), and central nervous system complications (28%). The current study also differ from a study conducted in Malaysia where the majority of participants (61.25%) mentioned that diabetic foot ulcer is the most common complications of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, two other studies describe lack of knowledge pertaining to diabetes for example; a study conducted in Malaysia showed that around 58.1% of respondents had poor diabetes knowledge score among rural adult community [ 12 ]. Another Indian study, involving outpatients and inpatients showed that about 46% of diabetic patients had poor knowledge whereas interestingly 64% of non-diabetics had good knowledge regarding diabetes [ 13 ].…”
Section: Discussionmentioning
confidence: 99%